Information available in general practice/family medicine consultations: coding and annotations for future use - Santiago, Luiz Miguel (2015)
Objectives: assuming the mandatoriness of ICPC2 classification in every consultation, the objective of this study was to ascertain the frequency of this type of classification in past consultations. This analysis was performed using the Weed-SOAP method, where Subjective (S) is measured by classifications and annotations, Objective (O) by annotations, Avaliation (A) by classification, and Plan (P) by classification and annotations. Methods: a cross-sectional observational study was performed in October 2012, with a 95% confidence interval and 6% error margin, on a representative random sample of consultations conducted on 4 random days of 3 random months of the first semester of 2012, and data were analyzed using descriptive and inferential statistics. Results: among the sample of 318 consultations, 149 (46.9%) were with male patients and 61 (19.2%) were aged under 18 years, while 194 (61.0%) were aged 18 or above but under 65 years, after sorting by age groups and gender. In terms of S, 98.7% of consultations had an ICPC-2 classification and 47.2% had an annotation; in terms of O, 66.0% had an annotation demonstrating the state of the patient and 79.9% were explicit; in terms of A, 97.8% had a classification; and in terms of P, 96.5% had a classification and 23.0% had an annotation explaining the plan. There was no statistically significant difference by age group for the studied variables. However, for gender, women had more “Clear and explicit” annotations in S, and “Classification of plan” instances in P. Conclusion: more complete recall of information in consultations is required in order to gain better knowledge about individual consultations and patients for future use.